An Historical Background to The Coming and Spread of Islam and Christianity in The Malay Peninsula, And the Indonesian and Philippine Archipelagos - Cesar Adib Majul (Al-Jami'ah: Journal of Islamic Studies, 1975)
An all too common feature of history has been how such externally introduced cultur institution as religion, has served to move peoples from their parochial, self-contained communities into wider ones committed to universal values. As it were, both lslam and christianity, which are universal in intent, have served to induce peoples in southeast Asia to conceive of themselves as part of wider human communities that have transcended the limitations of race, language, region and geography. Yet, paradoxically, lslam and to a lesser extent christianity as well, have provided those very elements of identity which played a large part in the struggle of the Malay peoples against foreign domination. No full understanding of these peoples' political, economic, and social conditions as well as of their concomittant expectations and tendencies is possible without taking into account the spiritual framework within which they lived.